Tourism and labor absorption in Aceh province, Indonesia - Muhammad Nasir; Chahayu Astina (Proceedings of AICS - Social Sciences, 2013)
This paper is aimed to analyze the change in employment in tourism sector in Aceh Province. The analysis is based on secondary data on employment and tourism. The model used in the analysis is multiple linear regression with independent variables are tourism industry, foreign tourists and tourism object along the dependent variable is employment/labor absorption. Based on the research findings with the regression analysis, it is found that the amount of the tourism industry, foreign tourist and tourism object affect employment/the amount of labor absorption in Aceh Province with adjusted R-squared is 0.8267. Therefore, to promote the tourism industry and labor absorption in Aceh economy, the government intervention is needed in facilitating regulation in tourism sector and setting the effective minimum wage in the effort to create more employment especially in tourism sector.Keywords: tourism, tourism object, employment, and labor absorption.